2021
DOI: 10.3390/polym13030472
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive Model of Isotropic Magneto-Sensitive Rubber with Amplitude, Frequency, Magnetic and Temperature Dependence under a Continuum Mechanics Basis

Abstract: A three-dimensional nonlinear constitutive model of the amplitude, frequency, magnetic and temperature dependent mechanical property of isotropic magneto-sensitive (MS) rubber is developed. The main components of MS rubber are an elastomer matrix and magnetizable particles. When a magnetic field is applied, the modulus of MS rubber increases, which is known as the magnetic dependence of MS rubber. In addition to the magnetic dependence, there are frequency, amplitude and temperature dependencies of the dynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 79 publications
(109 reference statements)
0
10
0
Order By: Relevance
“…where J is the volume ratio between current and reference configurations [57]. For incompressible materials, J = 1 [58].…”
Section: Methodsmentioning
confidence: 99%
“…where J is the volume ratio between current and reference configurations [57]. For incompressible materials, J = 1 [58].…”
Section: Methodsmentioning
confidence: 99%
“…[250] Based on experimental studies, it has been demonstrated that the temperature effect on elastomers is most significant at temperatures close to the transition phase. [229] Ju et al [304] investigated both isotropic and anisotropic MREs fabricated with polyurethane (PU) as the matrix and CI particles under temperature variations ranging from 20 to 90 °C. The results indicated that an increasing temperature under the application of an external magnetic field has resulted in a pronounced MR effect for isotropic MREs than anisotropic ones.…”
Section: Temperature Effectmentioning
confidence: 99%
“…To further verify the generality of the proposed model, third-party testing data on PBX 9502 from [28] It should be noted that the results of model parameters in Equations ( 7) and ( 11) cannot be directly used for prediction purposes as those parameters are material specific. The reported data on PBX 9502 are used to fit the developed model using Equation (2) for tension and compression data at each of the temperatures, and the temperature dependence for both modes are obtained using Equation (3). The same least squares fitting scheme is used.…”
Section: Validation Using Third-party Datamentioning
confidence: 99%
“…By compounding different filler materials with polymer, new functional materials can be made, providing a viable technology for on-demand material design and engineering [ 1 ]. Applications of PBMs include, but are not limited to, polymer-bonded magnetics [ 2 , 3 ], energetics [ 4 , 5 ], aluminum [ 6 ], fiber [ 7 , 8 ], and many others [ 9 , 10 , 11 ]. To utilize those functional materials in critical applications, understanding their mechanical properties and deformation behaviors under different loading and temperature conditions is of great importance in meeting the basic design criteria.…”
Section: Introductionmentioning
confidence: 99%